The Hijazi Railway 1318 – 1326 / 1990 – 1908 (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Hijazi Railway is considered one of the many attempts by the Ottoman Empire to link the Arab states with it, and to stop the disintegration and collapse of the Ottoman Empire, through which it wanted to show its keenness on the feelings of Muslims and provide comfort for practicing their religious rites. But the line was not only important in terms of religion for the state, but a way to ensure the rapid presence of the state in the areas of the Arabian Peninsula in terms of the rapid transfer of forces and control of disturbances that may be by the tribes There, especially with the state's fear of the ambitions of Sharif Hussein, and the line is different from the rest of the railway lines in the state of being the only line by the Ottoman engineers without the use of European countries with privileges in this area . يعد الخط الحديدي الحجازي إحدى المحاولات العديدة التي أرادت بها الدولة العثمانية ربط الولايات العربية بها، ووقف حالات التفكك والانهيار في الدولة العثمانية، فمن خلاله أرادت إظهار حرصها على مشاعر المسلمين وتوفير سبل الراحة لممارسة أهم شعائرهم الدينية، فهو يوفر المال والجهد ويرضي المسلمين جميعاً ويدعم فكرة بقاءهم في ظل حكم السلطان العثماني، إلا أن الخط لم يكن مهما فقط من الناحية الدينية بالنسبة للدولة، بل شكل وسيلة تؤمن التواجد السريع للدولة في مناطق الجزيرة العربية من حيث النقل السريع للقوات والسيطرة على الاضطرابات التي قد تقوم بها القبائل هناك، خصوصا مع تخوف الدولة من طموحات الشريف حسين، والخط يختلف عن بقية خطوط السكك الحديدية في الدولة  بأنه الخط الوحيد الذي قام به المهندسون العثمانيون دون الاستعانة بالدول الأوربية صاحبة الامتيازات في هذا المجال.